PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - BENNY CHANDRA; ARIESTA TIKA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study is to obtain empirical evidence of several factors affecting firm value in companies listed on the Indonesia Stock Exchange (IDX). The independent variables used in this study are Corporate Social Responsibility, Firm Size, Firm Age, Leverage, Asset Growth, Return on assets, and Foreign Ownership on Firm Value. The data used in this study is quantitative data from non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This study employs a purposive sampling method, involving 227 companies, with a total of 676 data points that met the criteria and passed the outlier test. The results of the study indicate that, first, Corporate Social Responsibility, Firm Age, Leverage, and Return on assets have a significant effect on Firm Value. Second, Firm Size, Asset Growth, and Foreign Ownership do not have a significant effect on Firm Value.